The Luzula comosa complex (Luzula section Luzula, Juncaceae) in western North America - Zika, Peter; Wilson, Barbara; Kirschner, Jan (Phytotaxa, 2015)
Field and herbarium study of Luzula comosa and its allies revealed two taxa in western North America that were overlooked in recent years but are distinct and best treated as species. Luzula cascadensis, once considered a variety of Luzula campestris, is elevated to species rank. It inhabits montane wetlands from southern Washington to California, east to Idaho and Montana. It is distinguished from Luzula comosa by its elongate horizontal rhizomes, usually darker tepals, and wetter habitats. Luzula macrantha is raised to species rank and separated from Luzula subsessilis by differences in inflorescence architecture as well as the length of the tepals, styles, and anthers. Luzula macrantha is found in dry forest and openings from southern British Columbia to California. Lectotypes are designated for Luzula comosa var. laxa and Luzula comosa var. congesta. Descriptions, distribution maps, synonymy, a key, and illustrations are provided for members of the group.